2022
DOI: 10.1039/d2fo01165d
|View full text |Cite
|
Sign up to set email alerts
|

Black bean husk and black rice anthocyanin extracts modulated gut microbiota and serum metabolites for improvement in type 2 diabetic rats

Abstract: Black rice and black bean have not yet been fully investigated as healthy foods for their therapeutic effects on type 2 diabetes mellitus (T2DM). In this study, we aimed to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 62 publications
2
8
0
Order By: Relevance
“…Sure enough, a significant decrease in the content of SCFAs was observed in the psicose group, especially the propionate and butyrate, which were strongly responsible for Muc-2 secretion. Consistent with previous findings [45,46], Akkermansia and Lactobacillus were positively associated with the expression of Muc-2 coupled with the levels of propionate and butyrate, and significantly negatively associated with inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 92%
“…Sure enough, a significant decrease in the content of SCFAs was observed in the psicose group, especially the propionate and butyrate, which were strongly responsible for Muc-2 secretion. Consistent with previous findings [45,46], Akkermansia and Lactobacillus were positively associated with the expression of Muc-2 coupled with the levels of propionate and butyrate, and significantly negatively associated with inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 92%
“…Sure enough, a significant decrease in the content of SCFAs was observed in the Psicose group, especially the propionate and butyrate, which were strongly responsible for Muc-2 secretion. Consistent with previous findings 42,43 , Akkermansia and Lactobacillus were positively associated with the expression of Muc-2 coupled with the levels of propionate and butyrate, and significantly negatively associated with inflammatory cytokines.…”
Section: Spearman Correlation Analysissupporting
confidence: 92%
“…Vitisin A could effectively down-regulate HMGCR and up-regulate LDLR expression, especially in the high-dose group. Some in vivo studies revealed that blueberry anthocyanins, black bean husk and black rice anthocyanin extracts were also able to down-regulate the gene expression of hepatic HMGCR, thereby inhibiting the synthesis of cholesterol in the liver [ 41 , 42 , 43 ]. An anthocyanin-rich fraction has been proven to markedly enhance LDL cholesterol uptake by increasing the LDLR protein level [ 12 , 44 ].…”
Section: Discussionmentioning
confidence: 99%